2004
DOI: 10.1143/jjap.43.l176
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Resonance in Split Ring Resonators

Abstract: We experimentally investigated the resonance effect of planar metallic split ring resonators (SRRs) in the far-infrared region (FIR) ($10:6 mm). Experimental results indicated that they exhibit resonance around 10.6 mm, implying negative permeability in the FIR region. Furthermore, the ratio of effective dimensions of the SRR cell and the wavelength of the incident beam was around 1 which suggested a wide scale independence. This size tolerance is useful in realizing the meta-materials with negative indices of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Panina et al [76] have proposed the use of pairs of parallel metal sticks (with lengths ∼100 nm) periodically embedded in a dielectric medium as an effective medium with negative magnetism at infrared frequencies. Hsu et al [64] have claimed resonance with the original SRR at a wavelength of 10.6 µm. But the size of the SSR was 10.48 µm and the assumption of an effective medium would hardly be valid.…”
Section: Scaling To High Frequenciesmentioning
confidence: 97%
See 1 more Smart Citation
“…Panina et al [76] have proposed the use of pairs of parallel metal sticks (with lengths ∼100 nm) periodically embedded in a dielectric medium as an effective medium with negative magnetism at infrared frequencies. Hsu et al [64] have claimed resonance with the original SRR at a wavelength of 10.6 µm. But the size of the SSR was 10.48 µm and the assumption of an effective medium would hardly be valid.…”
Section: Scaling To High Frequenciesmentioning
confidence: 97%
“…This has become well known subsequently as the split ring resonator-SRR for short. The SRRs are the basis of most of the meta-materials exhibiting negative magnetic permeability today [4,5,[25][26][27][62][63][64].…”
Section: The Split Ring Resonatormentioning
confidence: 99%
“…As far as we know, this SRR array is the first negative µ material. Recently, experimental studies of magnetic properties of SRRs have been reported in the THz region [8], particularly at 30 THz (10 µm wavelength) [9], and 100 THz (3 µm wavelength) [10]. On the other hand, theoretical studies of SRR behavior have been done from THz to near-infrared region [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial-style structures with negative index of refraction ͑n = ͱ ͱ ͒ were initially constructed and tested at microwave frequencies. 3,4 They have since advanced through infrared, 5,6 and are now at a stage where direct applications are within reach. To date, these structures have largely been of the "wine-crate" construction, 7 which is an array of split-ring resonators ͑SRRs͒ and wires.…”
mentioning
confidence: 99%